Enrichment of surimi gels with water-in-oil emulsions formulated with virgin coconut oil and quercetin-loaded chitosan nanoparticles - Alemán, Ailén; Montero García, Pilar; Ramos, Sonia; Gómez Guillén, M. C. (Food Hydrocolloids, 2025)
Water-in-oil (W/O) emulsions of virgin coconut oil (VCO) containing quercetin-loaded chitosan nanoparticles were incorporated into Alaska pollock surimi gels to obtain a new product with unique texture and coconut flavour. Loading nanoparticles with quercetin increased particle size and enhanced antioxidant properties without altering the ζ potential. Unloaded and loaded nanoparticles improved the rheological stability and antioxidant properties of the corresponding emulsions (E-NP and E-NPQ, respectively) compared to a control emulsion prepared without nanoparticles (E-C). Both types of nanoparticles decreased the lipid digestibility of the emulsions, particularly reducing the bioaccessibility of lauric acid. Surimi gels containing E-C, E-NP and E-NPQ were characterised in terms of pH, water holding capacity, colour and mechanical properties. The addition of nanoparticle-containing emulsions increased gel strength but decreased both resilience and gumminess. The presence of emulsified VCO provided juiciness and an intense coconut flavour, which were very well-accepted by most panellists. The work was supported by Project AGL 2017-84161 funded by MCIN/AEI/10.13039/501100011033 and ERDF A way of making Europe; project PID 2020-116142RB-I00 funded by MCIN/AEI/10.13039/501100011033, and project 202070E218 funded by CSIC. Peer reviewed